A Novel Method for Gaining New Insight on Flows Over Inundated Landscapes. Issue 20 (19th October 2021) - van der Steeg, Shailesh; Xu, Haiqing; Torres, Raymond; Elias, Edwin P. L.; Sullivan, Jessica C.; Viparelli, Enrica; Shelley, David; Lakshmi, Venkataraman
Abstract: We present a novel approach for detecting surface water flows over flooded terrain. The approach requires a minimum of three stage measurements and can be applied to any inundated surface, across a range of temporal and spatial scales. This method creates new and robust opportunities for field observation and for validation of numerical simulations and remote sensing analyses. In this proof‐of‐concept study, we found that floodplain free surface gradients were particularly variable during sub‐bankfull inundation, including abrupt current reversals. Also, flow direction varied with stage and the rate of change in stage. The "triangular facet" approach provides a new type of mesoscale insight of flow processes over inundated landscapes, highlighting flow complexity. Moreover, the approach provides information on floods that represent a compromise between point velocimeter measurements and satellite remote sensing and it can provide substantial benefits to society by aiding in flood hazard and mitigation assessment and planning. Plain Language Summary: We present a new approach for estimating flow direction and speed over a flooded terrain using sets of three water level recorders arranged in a triangular configuration. The approach can be applied to any inundated surface and scaled as needed. The triangular facet method provides valuable field observations that can be used to assess the performance of numerical models or remote sensing data. In our application over an inundated floodplain, the approach revealed complex flow patterns in space and time, and it shows that flow configurations for a given water stage are not necessarily repeatable. In particular, during lower inundation depths, the flow directions were highly variable, including abrupt changes in flow direction. This work helps fill a knowledge gap with respect to circulation during floods that is critical to understanding hazard planning and mitigation, material cycling and floodplain processes, and functions and habitat sustainability. Key Points: Three depth sensors define an inundation free surface; the maximum gradient of the plane defines flow direction and magnitude Analysis of high‐resolution flows helps fill a knowledge gap with temporal and spatial dynamics of floodplain inundation The controlling factors of floodplain flow dynamics are stage, rate of change of stage, and inundation process